Euroscepticism and the use of negative, uncivil and emotional campaigns in the 2019 European Parliament election: A winning combination. (March 2022) - Nai, Alessandro; Medeiros, Mike; Maier, Michaela; Maier, Jürgen
Are Eurosceptic parties more likely to run negative, uncivil and emotional campaigns, as it is often intuitively argued? And with what consequences? In this article, we shed light on the effectiveness of these campaign strategies for Eurosceptic parties during the 2019 European elections. We argue that 'harsher' campaigns are 'in character' for Eurosceptic parties, and are as such more likely to be electorally successful for them. We use data from the 2019 European Parliament Elections Expert Survey, covering 191 unique parties, and show that, indeed, Eurosceptic parties are more likely to campaign in a harsh way, and more likely than Europhile parties to benefit electorally from it. All data and materials are openly available for replication.